Optimization of efficiency for power system using three phase AC to AC matrix converter with the algorithm of fuzzy controller - Hassan Farahan Rashag (Institute of Advanced Engineering and Science, 2019)
This paper suggested a new contribution of three phase AC to AC matrix converter MC via fuzzy logic controller FLC to enhance the whole system. However, the weakness of matrix converter is that the input- output voltage transfer is control to 87% for input and output waveform. Also, matrix converter is more sensitive to the trouble of input voltage which deteriorates the system performance. To overcome these problems, and to improve the efficiency of system, FLC with matrix converter is proposed to minimize the sensitivity to the load, and to increase voltage transfer. In this paper the currents a,b,c are converted to alpha and beta current via Clarke transformation . In this method two FLC are used. The error (between alpha current and reference current) (e) and the change of this error (de) will apply to first FLC. The output of FLC is actual alpha current. In the other hand, the error of beta current and the change of error are also passes through the second FLC to produce the actual beta current. The actual alpha and beta current is converted to direct and quadrature d-q current by park transformation. The d-q current is converted to (a, b, c) out currents by inverse park transformation, the results of this method express that the matrix converter with FLC is more capable, high accuracy with better efficiency as compared with conventional matrix converter system.